(untitled) (AmS-Skrifter, 2026)
In 1911, a most remarkable treasure find from the last third of the 3rd century was discovered in Suluc in Dobruja, Romania. It contained four Roman gold coins (Hostilian and Gallienus), the gold head of an emperor’s bust, two silver cups of the Leuna Type, a gold crossbow brooch and three gold arm rings. One of them is a snake-head arm ring of Hildebrand’s Type C. The treasure from Suluc is extraordinary, as a comparable composition does not exist elsewhere in the eastern part of the Roman Empire. There, deposits of the 3rd century mainly contained coins, and occasionally precious-metal jewellery. Silverware, on the other hand, has been deposited more frequently only since the 4th century. It is therefore possible that the find from Suluc was hidden by a non-resident in the Roman Empire. As some of the objects already were in second- or even third-hand use and obviously were worn as jewellery or as “trophies of war”, it is likely that the treasure is connected with the numerous Gothic incursions into the Roman Empire in the second half of the 3rd century.